ChemInform Abstract: A Rapid Microwave‐Assisted Solvothermal Approach to Lower‐Valent Transition Metal Oxides. Issue 5 (4th February 2014) - Moorhead‐Rosenberg, Zachary; Harrison, Katharine L.; Turner, Travis; Manthiram, Arumugam
Abstract Binary oxides such as V4O9, Mn3O4 or MnO, CoO, and Cu2O are prepared within a short reaction time of 30 min by reduction of V2O5, MnO2, Co3O4, or CuO with tetraethylene glycol under microwave irradiation at <300 °C.